Exploring the (Very Flat) Potential Energy Landscape of R−Br⋅⋅⋅π Interactions with Accurate CCSD(T) and SAPT Techniques1. Issue 49 (27th October 2016) - Riley, Kevin E.; Vazquez, Mariela; Umemura, Cole; Miller, Christopher; Tran, Khanh‐An
Abstract: Halogen bonds involving an aromatic moiety as an acceptor, otherwise known as R−X⋅⋅⋅π interactions, have increasingly been recognized as being important in materials and in protein–ligand complexes. These types of interactions have been the subject of many recent investigations, but little is known about the ways in which the strengths of R−X⋅⋅⋅π interactions vary as a function of the relative geometries of the interacting pairs. Here we use the accurate CCSD(T) and SAPT2+3δMP2 methods to investigate the potential energy landscapes for systems of HBr, HCCBr, and NCBr complexed with benzene. It is found that only the separation between the complexed molecules have a strong effect on interaction strength while other geometric parameters, such as tilting and shifting R−Br⋅⋅⋅π donor relative to the benzene plane, affect these interactions only mildly. Importantly, it is found that the C 6 v (T‐shaped) configuration is not the global minimum for any of the dimers investigated. Abstract : Going the distance : High‐level ab initio methods are used to investigate the relationship between interaction strength and geometric parameters in R−Br⋅⋅⋅C6 H6 interactions. It is found that the interaction depends strongly on the distance between molecules but only very weakly on other geometric parameters. The C 6 v structure is found not to be the global minimum.